2019
DOI: 10.1002/ajb2.1338
|View full text |Cite
|
Sign up to set email alerts
|

Damage to leaf veins suppresses root foraging precision

Abstract: Plants typically grow in soil in which resources (e.g., water and nutrients) are distributed heterogeneously (Farley and Fitter, 1999; Wei et al., 2017), and individual plants encounter both high-and low-quality resource patches (Wei et al., 2017). Not surprisingly, plants use multiple behavioral strategies to forage for patchy resources (Cahill and McNickle, 2011). The best-studied strategy is the ability to grow more roots (biomass, length, etc.) in highnutrient patches than in low-nutrient patches (Cahill a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In addition, when plants are suffering from nutritional deficiencies such as nitrogen and phosphate, the foraging response of plant roots is activated to enhance the absorption of mineral nutrients from soils [15,16]. Some studies have shown that stress responses or signals from leaves induce root foraging responses [17]. However, the signal pathways coordinating the nitrogen requirement in leaves with the root foraging response are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when plants are suffering from nutritional deficiencies such as nitrogen and phosphate, the foraging response of plant roots is activated to enhance the absorption of mineral nutrients from soils [15,16]. Some studies have shown that stress responses or signals from leaves induce root foraging responses [17]. However, the signal pathways coordinating the nitrogen requirement in leaves with the root foraging response are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some secondary meristems, especially the cambium and phellogen, often retain partial autonomy in small branches and branch tips. Root branching plasticity allows roots to accomplish foraging behaviour which is critical in their difficult task of finding water and mineral nutrition [65][66][67]. In the root foraging behaviour, root apices continually evaluate, in a context-dependent manner, the amount of nutrients and integrate this information in dependency of their neighbouring plants [68].…”
Section: Fundamental Differences Between Root and Shoot Organogenesismentioning
confidence: 99%
“…This is the main reason that root apex organogenesis, in contrast with shoot organogenesis, is developmentally postponed and depends more on the local environmental situation [68]. Importantly, root foraging behaviour is affected by damage to shoot organs [67], implying shoot-root communication via the vascular systems is involved in both root organogenesis and root apex foraging decisions.…”
Section: Fundamental Differences Between Root and Shoot Organogenesismentioning
confidence: 99%
“…It has a relatively larger root system than local legume species [37], but this did not confer any priority in foraging scale. Plantago asiatica has a similar foraging precision compared to local deciduous tree species, both of which are easily interrupted by herbivores [40]. Both B. pilosa and P. asiatica roots had high foraging scale potential in karst soils, but their root morphology may be reduced by high Ca.…”
Section: Introductionmentioning
confidence: 99%